Current treatment methods for purulent and burn wounds - A. M. Emelyanova; S. N. Styazhkina; V. G. Fedorov; A. V. Subbotin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
This article analyzes treatment of patients with burns complicated by connective tissue dysplasia. Histological examination of skin biopsy samples demonstrated an association between the grade of dysplasia and the processes of wound regeneration. We provided case reports describing patients with deep burns in functionally significant areas and their comprehensive treatment with cytokines.